Market Power, Intertemporal Permits Trading, and Economic Efficiency - Jiang, Minxing; Feng, Xingliang; Li, Liang (Frontiers in Energy Research, 2021)
Banking and borrowing (BB) system has been developed gradually in tradable permits market to role as an environmental management tool. One question naturally arises as to how it will impact the firms’ behaviors and efficiency in presence of market power in permits market. This paper considers market power in two cases: with BB and without BB system. The equilibrium behaviors of the firms are identified in two cases. The findings show that the producing and discharging behaviors of firms depend on permits price elasticity of output price in no BB system, while they only depend on growth rate of output price in BB system. Although both cases fail to obtain efficient solutions, the market with BB system is capable of alleviating the inefficiency arising from market power compared with that without BB system. The path of permits price satisfies Hotelling rule in the case of BB system, while it is closely related to the path of output price and output price elasticity of permits price in the case without BB system.